Acute rhabdomyolysis with severe polymyositis following ipilimumab-nivolumab treatment in a cancer patient with elevated anti-striated muscle antibody. Issue 1 (December 2016) - Bilen, Mehmet; Subudhi, Sumit; Gao, Jianjun; Tannir, Nizar; Tu, Shi-Ming; Sharma, Padmanee
Abstract Background Immune checkpoint inhibitors have revolutionized cancer therapy since these drugs target inhibitory pathways on T cells, which result in durable anti-tumor immune responses and significant overall survival for a subset of cancer patients. These drugs can also lead to toxicities, which require additional research to identify mechanisms of toxicities and biomarkers that can help to identify patients who will develop immune-related adverse events. Case presentation We describe the first case, to our knowledge, of a patient with metastatic urothelial carcinoma who developed acute rhabdomyolysis with severe polymyositis after treatment with combination immunotherapy consisting of ipilimumab plus nivolumab (Trial registration: NCT01928394. Registered: 8/21/2013). We found that this patient had an elevated pre-existing anti-striated muscle antibody titer, which was likely exacerbated with the immunotherapy treatment thereby resulting in the presentation of acute rhabdomyolysis and severe polymyositis. Conclusions This case suggests that immune-related adverse events may be linked to subclinical autoimmune conditions which highlights the need for additional studies to identify patients who are at risk for toxicities.